Inkonsistensi Struktur Abstrak dalam Penelitian Tindakan Kelas dan Artikel Penelitian Pendidikan: Systematic Literature Review - Iftitahur Rizqi Amaliyah; Tasya Faiqhotur Rosyidah; Nining Churiroh; Dita Ainul l Kamala; Imron Fauzi (Indo Publishing, 2026)
Research abstracts play a crucial role in scientific communication because they concisely summarize the main elements of a study. However, inconsistencies in abstract structure are still frequently found in educational research writing. This study aims to analyze structural inconsistencies and abstract writing strategies in Classroom Action Research (CAR) reports and educational research articles. This study employs a Systematic Literature Review (SLR) approach to synthesize prior research on abstract structure and rhetorical strategies in academic writing. Literature was sourced from the Scopus, ScienceDirect, Web of Science, and Google Scholar databases, covering publications from 2020 to 2025. Selected articles were analyzed using genre analysis and rhetorical move analysis, focusing on the five main components of an abstract: background, objectives, methods, results, and conclusions. The results indicate that inconsistencies primarily occur in the presentation of research objectives, methods, and conclusions, which are more frequently found in classroom action research reports. This study contributes to the field of academic writing and offers recommendations for improving the clarity and consistency of research abstracts.